Ansiedad y rendimiento en jóvenes deportistas de un club de fútbol en Fonseca - La Guajira (2024)
Sports anxiety is a really complex issue, because when a person is in this condition, there is a history of physical and neuropsychiatric stress created by training sessions and competitions. The purpose of this study was to identify the relationship between anxiety and performance in young athletes who are part of the Juninho de Fonseca-La Guajira soccer club. A quantitative method was used with a descriptive approach and a non-experimental cross-sectional design, corresponding to a sample of 16 athletes between the age range of 15 - 20 years from the club in question. In this study, evaluation instruments such as the CPRD Questionnaire were used, which focuses on five main aspects of sports performance: stress control, performance evaluation effect, motivation, mental strength and team cohesion. Similarly, the 17-item Competitive State Anxiety Inventory 2 (CSAI-2) questionnaire consists of three subscales: psychological anxiety, somatic anxiety, and self-confidence.